The Quranic Dimensions of The Palestinian Cause and Its Impact on The Sacrifices of Its People to Support The Truth Through The Battle of The Flood of Al-Aqsa - Ahed Ahmed Abu Al-Ata; Hanafi Imam (Sekolah Tinggi Ilmu Ushuluddin (STIU) Darul Hikmah, 2024)
This study examines the Qur'anic dimensions of the Palestinian cause and its profound impact on the sacrifices made by the people of Palestine in support of justice and the defense of Islamic holy sites. The study analyzes Qur'anic verses that highlight the principles of justice, patience, and jihad in the cause of God, and how these values are embodied in resisting occupation and confronting injustice. The study highlights the events of the Al-Aqsa Flood as a vivid example of these heroic sacrifices and examines the lessons learned from these events within their Qur'anic context. The study aims to clarify the strong link between the Islamic faith and the steadfastness of the Palestinian people, highlighting the pivotal role of faith in strengthening morale and perseverance in the face of challenges. It also examines how Qur'anic texts can be used to guide and inspire the Palestinian people toward steadfastness and resistance.